Molecular Epidemiology and Risk Factors of Carbapenemase-Producing Enterobacteriaceae Isolates in Portuguese Hospitals: Results From European Survey on Carbapenemase-Producing Enterobacteriaceae (EuSCAPE) - Manageiro, Vera; Romão, Raquel; Moura, Inês Barata; Sampaio, Daniel A.; Vieira, Luís; Ferreira, Eugénia; , the Network EuSCAPE-Portugal; Caniça, Manuela (Frontiers in Microbiology, 2018)
In Portugal, the epidemiological stage for the spread of carbapenemase-producing Enterobacteriaceae (CPE) increased from sporadic isolates or single hospital clones (2010–2013), to hospital outbreaks, later. Here we report data from a 6-month study performed under the European Survey on Carbapenemase-Producing Enterobacteriaceae (EuSCAPE). During the study period, 67 isolates (61 Klebsiella pneumoniae and 6 Escherichia coli) non-susceptible to carbapenems were identified in participant hospital laboratories. We detected 37 blaKPC–type (including one new variant: blaKPC–21), 1 blaGES–5, and 1 blaGES–6 plus blaKPC–3, alone or in combination with other bla genes. Bioinformatics analysis of the KPC-21-producing E. coli identified the new variant blaKPC–21 in a 12,748 bp length plasmid. The blaKPC–21 gene was harbored on a non-Tn4401 element, presenting upstream a partial ISKpn6 (ΔISKpn6/ΔtraN) with the related left IR (IRL) and downstream a truncated Tn3 transposon. PFGE and MLST analysis showed an important diversity, as isolates belonged to distinct PFGE and STs profiles. In this study, we highlighted the presence of the high-risk clone E. coli sequence-type (ST) 131 clade C/H30. This worldwide disseminated E. coli lineage was already detected in Portugal among other antibiotic resistance reservoirs. This study highlights the intra- and inter-hospital spread and possible intercontinental circulation of CPE isolates.